A new chaotic attractor with two quadratic nonlinearities, its synchronization and circuit implementation - Vaidyanathan, S.; Sambas, A.; Sukono, .; Mamat, M.; Gundara, G.; Sanjaya, W.S.M.; Subiyanto, . (2018)
A 3-D new chaotic attractor with two quadratic nonlinearities is proposed in this paper. The dynamical properties of the new chaotic system are described in terms of phase portraits, equilibrium points, Lyapunov exponents, KaplanYorke dimension, dissipativity, etc. We show that the new chaotic system has three unstable equilibrium points. The new chaotic attractor is dissipative in nature. As an engineering application, adaptive synchronization of identical new chaotic attractors is designed via nonlinear control and Lyapunov stability theory. Furthermore, an electronic circuit realization of the new chaotic attractor is presented in detail to confirm the feasibility of the theoretical chaotic attractor model.